KAJIAN AWAL PENGEMBANGAN METODE ANALISIS ION SULFAT BERBASIS ONE DROP FLOW INJECTION ANALYSIS (OD-FIA) - Riptono, Agus
The analytical methods are generally high-cost, time and chemicals consuming. The usage of these chemicals makes the laboratory becomes the source of environmental pollutions. Flow Injection Analysis (FIA) method is a solution for reducing the high usage of chemicals since its measurement is less time consuming and it does not need to reach the real system equilibrium. An analysis protocol for sulfate ion using one drop FIA method with spectrophotometric detection technique using optical fiber equipment was developed and evaluated. The evaluation results in a high analytical performance of the method, shown by the reproducibility values of 7.14% and 1.96% for concentration of 25 ppm and 125 ppm, respectively. Calibration curve showed a good linearity at the concentration range of 25 to 125 ppm with the approximate correlation value of 1. This method was applied to analyze the sulfate ion concentration in water from Jatiluhur dam.